Survey research methods - Fowler, Floyd J
Includes bibliographical references and index; Types of errors in surveys -- Sampling -- Nonresponse: implementing a sample design -- Methods of data collection -- Designing questions to be good measures -- Evaluating survey questions and instruments -- Survey interviewing -- Preparing survey data for analysis -- Analyzing survey data -- Ethical issues in survey research -- Providing information about survey methods -- Survey error in perspective